Continuum centroid classifier for functional data. Issue 1 (13th July 2021) - Zhou, Zhiyang; Sang, Peijun
Abstract : For the binary classification of functional data, we propose the continuum centroid classifier (CCC), which is constructed by projecting the functional data onto one specific direction. This direction is obtained via bridging the regression and classification. Our technique is neither unsupervised nor fully supervised; instead, we control the extent of the supervision. Thanks to the intrinsic infinite dimension of functional data, one of the two subtypes of CCC enjoys an (asymptotic) zero misclassification rate. Our approach includes an effective algorithm that yields a consistent empirical classifier. Simulation studies demonstrate the competitive performance of the CCC in different scenarios. Finally, we apply the CCC to two real examples. Résumé : Pour la classification binaire de données fonctionnelles, les auteurs proposent le classificateur au continuum du centroïde (CCC) qui est construit en projetant les données fonctionnelles sur une direction spécifique obtenue en faisant le relais entre la régression et la classification. La technique des auteurs n'est ni entièrement supervisée, ni non supervisée, puisqu'ils contrôlent l'ampleur de la supervision. Grâce à la dimension intrinsèque infinie des données fonctionnelles, l'un de deux sous‐types de CCC présente un taux (aymptotique) nul de mauvaise classification. Les auteurs décrivent un algorithme efficace qui donne un classificateur empirique convergent. Ils démontrent par des simulations que le CCC offre des performances compétitives sous différents scénarios. Finalement, ils appliquent le CCC à deux exemples réels.